PARKING GOVERNANCE IN PERSPECTIVE PUBLIC SPHERE (CASE STUDY OF ILLEGAL PARKING IN BANDUNG CITY) - Gunawan, Wawan; Yovinus, Yovinus; Dena Fritiar, Inkha Hedian (Universitas Jenderal Ahmad Yani, 2024)
Illegal parking has become a problem in the city of Bandung that never ends. The limitation of parking spaces is one of the causes. There are no strict sanctions against illegal parking attendants, causing illegal parking to mushroom. In addition to illegal parking eating up a lot of public facilities and narrowing the public sphere, illegal parking has an impact on the practice of thuggery that disturbs the community. Starting from parking fee hikes, to acts of persecution and even murder. Murder has occurred in the city of Bandung due to the fight for (illegal) parking lots, and resulted in the road body getting narrower and the congestion severe. It has a negative impact on public comfort, order and safety. Illegal parking is a serious problem that must be immediately fixed by the Bandung City government. If not corrected immediately, it will have a negative impact on people's lives and hinder the development process of the city of Bandung. The practice of illegal parking is getting 'wilder' and rampant in the city of Bandung, causing losses to the community. Illegal parking in the community causes people to be uneasy, even feeling intimidated by this legal practice. The phenomenon of parking fee hikes carried out by illegal parking attendants has become a difficult condition for the Bandung city government to abolish which does not act firmly. Illegal parking makes a lot of use of the space of the road body, resulting in the road getting narrower and causing long traffic jams. The Bandung city government has a lot of government land that can be used as an official parking lot. Like the former Palaguna land in the Bandung city square area, it can be collaborated with the private sector in the Build Operate Transfer (BOT) scheme. So that public spaces can be functioned optimally by the people of the city of Bandung. Conditions have a positive impact on people's lives. The level of congestion has decreased positively by reducing the level of stress and unrest of the community. maximizing the function of public spaces, not as a recreational space, but as a means of education, creativity, so as to foster a better democratic climate for the community.